Pelatihan Internet dan Pengenalan E-Commerce Bagi Masyarakat Desa Ciaruteun Ilir Bogor - rosida nur aziza; Abdul Haris; Rahma Farah Ningrum; Puji Catur Siswipraptini; Karina Djunaidi; Abdurrasyid Abdurrasyid; Riki Ruli Siregar (Terang, 2019)
Ciaruteun Ilir is a village in the District of Cibungbulang, Bogor. It is located approximately 25 kilometres from the capital of the Bogor Regency. The average population, mostly farming, is on the poverty line and has a low level of education. Formal education facilities are still very limited. Therefore, training and courses from the government and other parties are needed to increase the knowledge, broaden their mind, and improve the skills of the population. The courses that are organized are expected to increase the villagers’ income. While broader mind is expected to increase citizens' awareness of the importance of education. The PKM (Program Kemitraan Masyarakat or community service program) team intends to provide training related to Information Technology to the public, especially regarding the introduction of the Internet. The public will be introduced to the Internet and E-Commerce, which is one of the Internet applications that allows buying and selling transactions through the Internet network. The internet will open opportunities for citizens to increase knowledge and learn from various sources. With E-Commerce training, villagers will be equipped with the ability to be able to introduce products from their villages and doing commercial transactions via the Internet.